Development of a SYBR Green-Based RT-qPCR Assay for the Detection and Quantification of Lone Star Virus - Megan Burch; Jeremy Bechelli (Zoonoses)
Lone Star virus (LSV) is a newly characterized arbovirus with pathogenic potential. However, no detection methods are available to specifically identify and monitor LSV. Two SYBR green-based RT-qPCRs were developed and validated for the detection and quantification of LSV. Two primer sets were evaluated for reproducibility, specificity, and sensitivity. The primer sets were applied to monitor viral titers in vitro and via surveillance of LSV in collected ticks. One primer set (LSV-S) was the most specific for LSV when tested against 11 other vector-borne viruses. While less specific, the LSV-M primer set detected <2 copies/μl of the viral genome and <1 copy/μL of the viral genome. Viral replication quantified with either primer set yielded similar viral replication patterns, indicating that both primer sets are sufficient to monitor viral titers in vitro . Plaque assays in human and non-human primate cell lines yielded no replicable plaques and could not be used for comparisons of viral titer quantification. LSV was not detected in the 143 ticks collected from southeast Texas. The SYBR green-based RT-qPCRs described herein can be utilized for the detection and monitoring of LSV for laboratory and tick surveillance purposes.